2015
DOI: 10.1016/j.metabol.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Accumulating exercise and postprandial health in adolescents

Abstract: Purpose: To examine the influence of exercise intensity on postprandial health outcomes in adolescents when exercise is accumulated throughout the day. Methods: 19 adolescents (9 male, 13.7 ± 0.4 y) completed three 1-day trials in a randomised order: 1) rest (CON); or four bouts of 2) 2 x 1 min cycling at 90% peak power with 75 s recovery (high-intensity interval exercise; HIIE); or 3) cycling at 90% of the gas exchange threshold (moderate-intensity exercise; MIE), which was work-matched to HIIE. Each bout was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Our findings therefore, go beyond earlier work by reporting substantial improvements in triglycerides (-26%) from a representative adolescent sample that consisted of ‘under’, ‘normal’ and ‘overweight/obese’ males and females. While the mechanisms behind HIT-induced decreases in triglycerides are unclear, recent work suggests this may be due to decreases in the postprandial lipaemic response [ 56 , 57 ] and/or increases in postprandial resting fat oxidation [ 58 , 59 ]. The former theory is in light of research by Thackray et al [ 56 ], where changes in adolescent boys’ fasting plasma triglyceride concentration were small to moderate (mean difference -0.05 mmol/L; 95% confidence interval -0.11 to 0.01 mmol/L; effect size 0.40) following a single running-based HIT session (10 x 60 s efforts at maximal aerobic speed, each interspersed with 60-s recovery).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings therefore, go beyond earlier work by reporting substantial improvements in triglycerides (-26%) from a representative adolescent sample that consisted of ‘under’, ‘normal’ and ‘overweight/obese’ males and females. While the mechanisms behind HIT-induced decreases in triglycerides are unclear, recent work suggests this may be due to decreases in the postprandial lipaemic response [ 56 , 57 ] and/or increases in postprandial resting fat oxidation [ 58 , 59 ]. The former theory is in light of research by Thackray et al [ 56 ], where changes in adolescent boys’ fasting plasma triglyceride concentration were small to moderate (mean difference -0.05 mmol/L; 95% confidence interval -0.11 to 0.01 mmol/L; effect size 0.40) following a single running-based HIT session (10 x 60 s efforts at maximal aerobic speed, each interspersed with 60-s recovery).…”
Section: Discussionmentioning
confidence: 99%
“…The former theory is in light of research by Thackray et al [ 56 ], where changes in adolescent boys’ fasting plasma triglyceride concentration were small to moderate (mean difference -0.05 mmol/L; 95% confidence interval -0.11 to 0.01 mmol/L; effect size 0.40) following a single running-based HIT session (10 x 60 s efforts at maximal aerobic speed, each interspersed with 60-s recovery). More recently, Bond et al [ 59 ] reported that a single HIT bout performed via cycle ergometry (8 x 60 s efforts at 90% of peak power, interspersed with 75 s recovery) increased resting postprandial fat oxidation in adolescent males and females (aged 13 to 14 years), in the four hours subsequent to consuming a high fat meal. As such, whilst it was not our intention to explore the mechanisms underpinning the triglyceride reductions in our study, it could be hypothesised that the chronic reductions occurred as a result of the acute responses detailed above.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, data indicate that an acute bout of HIIE has the potential for attenuating postprandial lipemia in young people, although these benefits are likely to be observed the day after the exercise bout, 33 35 thereby implicating a key role for the delayed increase in lipoprotein-lipase activity. Currently, the large differences in the HIIE dose, timing and composition of test meals, and lack of mechanistic insight mean that it is not possible to identify how HIIE may be optimized to modify postprandial lipemia.…”
Section: Acute High-intensity Exercise and Health Outcomesmentioning
confidence: 98%
“…Currently, the large differences in the HIIE dose, timing and composition of test meals, and lack of mechanistic insight mean that it is not possible to identify how HIIE may be optimized to modify postprandial lipemia. However, postprandial lipemia is not attenuated post-HIIE in adolescents, despitea ~20% increase in resting fat oxidation during the postprandial period, 34 , 35 demonstrating that these outcomes are unrelated when exercise is performed the same day as the test meal, although this might not be the case the following day. 31 An increase in postprandial 3-hydroxybutyrate after HIIE was associated with lower TAUC-TAG in one adolescent study, 33 suggesting that intensity-dependent changes in hepatic very-low-density lipoprotein output might play some as-yet-unexplored role in this group.…”
Section: Acute High-intensity Exercise and Health Outcomesmentioning
confidence: 98%
“…Time-efficient, high-intensity interval exercise (HIIE) has been shown to improve cardiorespiratory fitness and cardiometabolic risk factors such as insulin sensitivity (IS), fasting glucose and insulin in youth [14,23]. Furthermore, recent research has shown improvements in glucose and insulin health outcomes after a single bout of HIIE [4,10,41] and are either superior [4] or comparable [10] to work-matched moderate-intensity exercise (MIE). Howev-…”
Section: Introductionmentioning
confidence: 99%